A dopant-free hole transport material boosting the performance of inverted methylamine-free perovskite solar cells. Issue 6 (17th January 2022) - Wan, Li; Tan, Yulin; Zhao, Yang; Lou, Lingyun; Wang, Zhong-Sheng
Abstract : A polymer PFDTS is adopted as a dopant-free hole-transport material for inverted methylamine-free perovskite solar cells, which achieves a power conversion efficiency of 20.15% with good air and thermal stability. Abstract : Great progress in power conversion efficiency (PCE) of methylamine (MA)-free inverted perovskite solar cells (PSCs) is inseparable from the rapid development of hole transport layers (HTLs). We design and synthesize a polymer called PFDTS with a suitable energy level to match the energy level of perovskite. Furthermore, by virtue of the interactions of the carboxylic acid groups on the side chains of the PFDTS molecule with the indium tin oxide substrate and perovskite, perovskite can form compact and uniform films on the HTL surface. Therefore, the inverted MA-free PSC based on PFDTS as the HTL can obtain a PCE of 20.15%, a 10% enhancement relative to the control device based on PTAA that is widely used in inverted PSCs. In addition, the PFDTS-based device also shows better air and thermal stability than the PTAA-based device. The PFDTS-based device maintains 91% of the initial PCE against 75% for the PTAA-based device after storing under the ambient conditions for 1000 h. The former retains 80% of the initial PCE against 66% for the latter after continuous heating at 85 °C for 500 h. It can be seen that PFDTS is a promising hole transport material for MA-free inverted PSCs.